Sources and Treatment Methods of Excessive Manganese Ion in Groundwater in A Certain Area - Wang, Zhiqiang (International Journal of Natural Resources and Environmental Studies, 2024)
Trace element manganese is an essential element for human body, but the high concentration of manganese will adversely affect human health and all aspects of daily production and life. Elevated levels of manganese directly affect the color of the water, making it more prone to discoloration when used to wash clothes or dishes. Prolonged exposure to this water may cause organ damage. The groundwater in the study area is sampled and tested, and the test data is analyzed. The main results are as follows: the groundwater manganese ions in the study area exceed the standard, and the concentration of manganese ions in the southwest mountainous area is higher than that in other areas. In southwest China, due to the planting of a large number of tea trees, the main source of manganese in groundwater is manganese-containing fertilizer, and sewage recovery and treatment should be considered in combination with slope rainwater recovery equipment. In other fields, the manganese in groundwater is mainly from domestic sewage. The combined treatment of manganese ions in groundwater by chemical method and contact oxidation method is considered.